Anxiety as a Mediator in the Relationship between Psychological Inflexibility and Academic Procrastination among College Students - Yang, Valencia; Oriza, Imelda Ika Dian (Universitas Medan Area, 2025)
Academic procrastination is a common issue among college students that may negatively impact academic achievement and psychological well-being. This study aimed to investigate the role of anxiety in the form of trait anxiety as a mediator between psychological inflexibility and academic procrastination among college students. A total of 183 college students aged 18-25 years (M = 20,28) participated in the study by completing the Acceptance and Action Questionnaire-II (AAQ-II), the State-Trait Anxiety Inventory (STAI), and the Academic Procrastination Scale (APS). Based on the result of a simple mediation analysis using PROCESS Macro v 4.2, it was found that trait anxiety partially mediates the relationship between psychological inflexibility and academic procrastination. This finding indicates that psychological inflexibility is related to academic procrastination whether directly or indirectly through the mediation of trait anxiety. This study highlights the importance of psychological interventions targeting psychological flexibility enhancement and anxiety regulation to reduce academic procrastination among students.